Vasoactive intestinal peptide alleviates food allergy via restoring regulatory B cell functions - Zeng, Hao-Tao; Zhao, Miao; Yang, Shao-Bo; Huang, Huang; Geng, Xiao-Rui; Liu, Jiang-Qi; Yang, Gui; Li, Dong-Cai; Yang, Li-Tao; Zheng, Peng-Yuan; Yang, Ping-Chang (Immunobiology (1979), 2019)
The immune regulatory cell dysfunction is associated with many immune diseases including food allergy (FA). This study aims to investigate the role of vasoactive intestinal peptide (VIP) in the maintenance of regulatory B cell (Br cell)'s immune suppressive functions by stabilizing thrombospondin (TSP1) expression. In this study, blood samples were collected from patients with food allergy (FA) and healthy control (HC) subjects. Br cells were isolated from the samples through flow cytometry cell sorting and analyzed by immunological approaches to determine the immune regulatory capacity. We found that the immune suppressive functions of Br cells were impaired in FA patients. The serum VIP levels were associated with the production of immune suppressive function-related mediators (interleukin-10, IL-10) of Br cells in FA patients. VIP counteracted IL-10 mRNA decay in Br cells by up regulating the TSP1 expression. TSP1 inhibited tristetraprolin (TTP) to prevent IL-10 mRNA decay in Br cells. Administration of VIP inhibited FA response through restoration of immune suppressive functions in Br cells. In conclusion, administration of VIP can alleviate FA response through up regulating expression of TSP1 to stabilize IL-10 expression in FA Br cells and recover the immune regulatory functions. The results have translational potential for the treatment of FA and other disorders associated with immune regulatory dysfunction of Br cells.